102k views
3 votes
Simplify the expression. y^2Y^3/y^Y-2 a y^5 b y^4 c y^3 s y^6

User Dimsuz
by
4.8k points

1 Answer

4 votes

Answer:

I guess that the expression is:

(y^2*y^3)/(y*y^(-2))

remember this two relationships.

a^x*a^y = a^(x + y)

(a^x)/(a^y) = a^(x - y).

then we have:

y^2*y^3 = y(2 + 3) = y^5.

and

y*y^(-2) = y^(1 + (-2)) = y^-1

then our expression can be written as:

(y^2*y^3)/(y*y^(-2)) = y^5/y^(-1) = y^(5 - 1) = y^4.

Then the correct option is b: y^4

User JoeyG
by
4.9k points